Optimization of extraction and enrichment process of cannabidiol from industrial hemp and evaluation of its bioactivity - Wu, Junkai; Zhang, Xiaomeng; Liu, Xiaoqing; Sheng, Zunlai; Hu, Jianping; Zhang, Feiyan (Frontiers in Plant Science, 2025)
IntroductionThe Cannabis Sativa L., a perennial dioecious herb renowned for its industrial applications, serves as the source of hemp. Cannabidiol (CBD), a non-psychotropic compound derived from industrial hemp, has garnered considerable interest due to its promising therapeutic potential.MethodsThe extraction parameters for CBD from industrial hemp were optimized using the Box-Behnken design and response surface methodology (RSM). The purification process involved characterizing the penetration and desorption profiles of CBD on HPD-100 resin. The in vitro antibacterial activity was assessed by determining the minimum inhibitory concentration (MIC) against Staphylococcus aureus and Escherichia coli. Antioxidant properties were evaluated using DPPH and ABTS assays, as well as an iron-reducing ability test.ResultsAfter optimization, the extraction rate of CBD reached 0.26 ± 0.02%. The use of HP-100 resin in the purification process resulted in a significant enrichment of CBD content, which was 4.2 times higher than that of the crude extract, with a recovery rate of 83.13%. The MIC against S. aureus was found to be 5 mg/mL, while no inhibitory effect was observed against E. coli. The IC50 values for the DPPH and ABTS assays were 0.1875 mg/mL and 2.988 mg/mL, respectively, indicating the potent antioxidant capacity of CBD. Additionally, CBD demonstrated a strong iron-reducing ability.ConclusionThese findings contribute to the development of CBD for broader applications in various industries, highlighting its potential as a valuable compound in health and wellness sectors.